The rise of finance : causes, consequences and cures - Nageswaran, V. Anantha; Natarajan, Gulzar (Cambridge : Cambridge University Press, 2019)
Financialisation, or the disproportionate importance of financial considerations in economic decisions, has been a defining feature of the economic history of the last twenty-five years. The wave of deregulation that accompanied the neoliberal agenda in the US, aided by the dominance of US dollar and American economy, has resulted in the globalisation of finance. This book examines the rise of financialisation globally, while charting its drawbacks and prescribing suggestions for a definitive overhaul of the structure. Bringing together various strands of the latest research and evidence generated in recent years, empirical analysis, and views of reputed experts in the field, it presents a counter-point to the canonical ideas of analysing financial market dynamics and financial globalisation. It proposes a revision of the current monetary policy paradigm to correct its excessive focus on equity markets and their 'wealth effect', embrace a more symmetric response to the economic cycle, and a mandate to focus on financial stability as much as price stability.
Title from publisher's bibliographic system (viewed on 09 May 2019).
Keywords: Finance; Globalization